1989
DOI: 10.1002/ejsp.2420190604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social comparison information on learned helpless and mastery‐oriented children in achievement settings

Abstract: The present study investigates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…However, in reviewing the literature, we also found that social comparison in the classroom-in particular, upward comparison-may enhance negative affect (e.g., Bossong, 1985;Butler, 1989;Buunk et al, 2005;Hokoda et al, 1989) and lower academic self-concept (e.g., Crabtree & Rutland, 2001;Dickhäuser & Galfe, 2004;Felson & Reed, 1986; for studies on the BFLPE, see Marsh, 1984, e.g. ) by reminding students that they are inferior.…”
Section: Resultsmentioning
confidence: 77%
“…However, in reviewing the literature, we also found that social comparison in the classroom-in particular, upward comparison-may enhance negative affect (e.g., Bossong, 1985;Butler, 1989;Buunk et al, 2005;Hokoda et al, 1989) and lower academic self-concept (e.g., Crabtree & Rutland, 2001;Dickhäuser & Galfe, 2004;Felson & Reed, 1986; for studies on the BFLPE, see Marsh, 1984, e.g. ) by reminding students that they are inferior.…”
Section: Resultsmentioning
confidence: 77%
“…For example, people who are afraid of, or anxious about failure in challenging and demanding situations, and therefore seek to avoid them, are shown to be low achievers (Jones & Berglas, 1978; Midgley, Arumkumar & Urdan, 1996; Miller, 1987). On the other hand, those who are optimistic and make an active effort to deal with a challenging situation turn out to be high achievers (Aspinwall & Taylor, 1997; Cantor, 1990; Diener & Dweck, 1978; Hokoda & Fincham, 1995; Hokoda, Fincham & Diener, 1989; Pintrich & DeGroot, 1990). Another important factor that has been shown to influence adolescents’ academic achievement and problems at school is their peers and friends.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, future studies may explore potential moderators of the relationship between social comparison and academic achievement. Possible moderators are, for instance, the level of psychological closeness (Guay, Boivin & Hodges, 1999;Huguet et al, 2001), attributional style (e.g., Hokoda, Fincham & Diener, 1989) and reciprocity of comparison choices (Lubbers et al, 2009).…”
Section: Discussionmentioning
confidence: 99%